Perizinan Usaha Wisata Kawasan Karst Gunung Sewu: Diskresi Penataan Ruang Dan Ancaman Lingkungan Hidup - Novikasari, Siti Rahma; Murti, Aditya Khrisna (UI Scholars Hub, 2025)
The Gunung Sewu Karst Area is located in Gunungkidul, Wonogiri, and Pacitan Regencies. It has a unique geological formation so it was designated as a Global Geopark by the United Nations Education Scientific and Cultural Organization (UNESCO) in 2015. However, the Gunungkidul Regional Government is targeting the regional economy condition by proposing to reduce the number of karst landscape area and granting tourism business permits. These actions had serious impacts on geological, hydrological and ecological conditions. Therefore, this study aims to examine: 1) How is the conformity between tourism business permits and spatial planning provisions for the karst area? 2) What are the legal consequences of tourism business permit that conflict with spatial planning provisions? The doctrinal legal research is used to examine legal issues with a statutory and conceptual approach. Qualitative descriptive methods are used to analyze secondary data. The results of this study indicate that tourism business permits issued by the Gunungkidul Regional Government violate the Zoning Direction Indications for Geological and Tourism Protected Areas and Special Provisions for Karst Areas. Tourism business permits issued by the Gunungkidul Regional Government were categorized as the government's discretion, so the principle of Het Vermoden van Rechtmatigheid and Contrarius Actus Similiter Fit applied. Keywords: Discretion, Karst Area, Tourism Business Permit